Strategi Komunikasi Program Sosialisasi dan Komunikasi Untuk Meningkatkan Citra Perusahaan PT Agincourt Resources Tambang Emas Martabe - Windi Wulan Dari; Muhamad Fajri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
PT Agincourt Resources is a mining company based in Indonesia engaged in the exploration, mining and processing of gold and silver bar minerals. The company PT Agincourt Resources received rejections from the community so that the demonstration occurred due to the disposal of waste which would be directed to the Batangtoru River and other issue that could cause a decline in the company’s image. So that from this incident the Community Relations departement formed a Socializations and Communication Program as a bridge and forum for the community so that misunderstandings in communications and cons from the public against the company do not occur. The aim of the Socialization and Communications Program is to provide positive informations to the community related to mining through socialization activies which explain that the waste dischargerd into the Batangtoru River is not waste but residual water from the processing process.